Wedding night [compact disc, unabridged] : a novel - Kinsella, Sophie (Random House Audio : Books on Tape, 2013)
Lottie is 33, and is sick of boyfriends who don't want to commit to marriage. When her old boyfriend Ben reappears after fifteen years and reminds her of their pact to marry each other if they are both single after 30, Lottie jumps at the chance. But not everyone is pleased with Lottie and Ben's arrangement, and family and friends are determined to intervene. Will they make Lottie and Ben's wedding night one to remember--or one to forget?